Konstitusionalitas Perlindungan Hukum bagi Orang dengan Gangguan Jiwa di Indonesia - Hafid Ma’ruf Haqiqi, Hafid Ma’ruf Haqiqi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Human rights apply to every individual regardless of condition, including people with mental disorders (ODGJ) who hold equal status before the law (equality before the law). However, observations in Pekalongan City show that many ODGJ remain neglected on the streets without adequate protection from responsible parties. As Indonesian citizens, they are entitled to access medical treatment and a decent standard of living. This study aims to analyze legal protection for the constitutional rights of ODGJ and to identify the factors influencing such protection. The research employs an empirical legal approach combined with statutory and qualitative approaches. Data were collected through interviews, observation, and documentation, then analyzed using an interactive model. The findings reveal that legal protection for ODGJ by the Pekalongan City Government consists of two forms: preventive (prevention) and repressive (law enforcement). Although these efforts are implemented, their execution remains suboptimal and still faces shortcomings. The factors influencing the protection of ODGJ’s constitutional rights, based on Lawrence M. Friedman’s legal system theory, include legal substance (regulations that are not fully clear and applicable), legal structure (limited implementing institutions), and legal culture (stigmas and low public awareness regarding the rights of ODGJ).